Ghostly Goings On. Can Ghost Stories Provide the Perfect Allegory for Loneliness and Neglect in Children’s Writing? - Nell Griffin (Leaf Journal)
It could be argued that the popularity of ghost stories for young readers (seen most clearly in the Middle Grade age bracket) is due to a demand for ‘age appropriate’ horror novels for a younger readership, eager to lap up spooky tales. However, could there be more going on than meets the ‘pale blue eye’?